2013
DOI: 10.1002/cbin.10061
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Smad2 activity shows resistance to TGF‐β signalling in mammary adenocarcinoma (MCF‐7) cells

Abstract: Transforming growth factor-β (TGF-β) is a potent inhibitor of the growth of normal mammary epithelial cells, and has a pleiotropic, context-dependent, concentration-dependent action. We found attenuation of TGF-β signalling in mammary adenoma carcinoma cells. Phosphorylation at the linker site of Smad2 occurred in a cooperative way during the attenuation of TGF-β signalling, and was associated with upregulation of CDK2 and cyclin D1. CDK2 inhibitor restored the anti-proliferative effect of TGF-β by upregulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…They are induced by TGF-beta and result in cell cycle arrest through associating with their target cyclin-CDK complexes [3]. However, in many cancers, the cancer cells are resistant to the inhibitory effects of TGF-beta [4][5][6]. Instead of inhibiting growth, TGF-beta promotes tumor malignance and invasion [7].…”
Section: Introductionmentioning
confidence: 98%
“…They are induced by TGF-beta and result in cell cycle arrest through associating with their target cyclin-CDK complexes [3]. However, in many cancers, the cancer cells are resistant to the inhibitory effects of TGF-beta [4][5][6]. Instead of inhibiting growth, TGF-beta promotes tumor malignance and invasion [7].…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, as a member of the transforming growth factor β family, TGF-β works as a multi-functional cytokine and plays an important role in cell proliferation, apoptosis and differentiation [29]. TGF-β is an important gene that has been identified as a cancer susceptibility gene that exerts tumor-suppressive effects that cancer cells must elude for malignant evolution [29][30][31][32]. TGFBR1 and TGFBR2-two transmembrane serine/threonine kinase receptors, are required for TGF-β signaling transduction.…”
Section: Discussionmentioning
confidence: 99%
“…It is held that miR-93-3p enhances the malignancy of ccRCC cells by stimulation of angiogenesis through down-regulation of PEDF [209]. Although it has been shown that TGF-β contributes to the induction of cell cycle arrest, accumulating data demonstrates that the resistance of cancer cells into TGF-β reverses its anti-tumor impact and this signaling pathway may enhance the progression of tumor cells [268][269][270][271][272]. The fundamental pathway involved in this function is various among different cancer types [273].…”
Section: Renal Carcinomamentioning
confidence: 99%